Is Europe Good for You? : EU Spending and Well-Being - Dellmuth, Lisa (Book collections on Project MUSE., 2021)
This important book investigates how the European Union (EU) can use its regional funding programmes in ways that increase citizen well-being. It argues the case for enhancing the inclusivity of EU growth, which yields the promise of a more legitimate and stronger union.